Effect of charge compensators (Li+, Na+, K+) on the luminescence properties of Sr3TeO6:Eu3+ red phosphor. Issue 6 (15th March 2021) - Ma, Yingying; Chen, Shigao; Che, Junzhi; Wang, Jianxu; Kang, Ruyi; Zhao, Jin; Deng, Bin; Yu, Ruijin; Geng, Huiling
Abstract: A double-perovskite Sr3 TeO6 :Eu 3+ red phosphor was successfully prepared and confirmed to be a single phase through X-ray diffraction. Under an optimal excitation wavelength (394 nm), the Sr3 TeO6 :Eu 3+ phosphor emitted intense red light at 617 nm, which corresponded to 5 D0 → 7 F2 transition. When the concentration of Eu 3+ exceeded the optimal doping concentration (25 mol%), concentration quenching occurred because of the interactions among the nearest neighbor ions. The phosphor exhibited excellent thermal stability, and the E a value was 0.27 eV. In accordance with Judd–Ofelt theory, the low symmetry of Eu 3+ ions was confirmed, and it resulted in a color purity of up to 99.5%–99.8%. Among the charge compensators (Li +, Na +, and K + ), the Na + ions had the best charge compensation effect. The luminescence intensity of Sr3 TeO6 :Eu 3+, Na + was approximately 2.06 times that of Sr3 TeO6 :Eu 3+ and 2.25 times that of commercial phosphor (Y2 O3 :Eu 3+ ). The fabricated red LED has the potential to be used for plant and herb cultivation. A white light–emitting diode (w–LED) was successfully prepared, and related parameters were established. The Ra value of the prepared w–LED was as high as 91, and R9 was 5.7 times that of a commercial w–LED. These characteristics indicate that phosphors have potential in the solid-state lighting field.